Monitoring financial risk and earnings manipulation across Malaysia, Thailand and Indonesia / Zakiyyah Jamaludin - Jamaludin, Zakiyyah (Faculty of Business and Management, 2018)
This paper has shown the tested results on the significance of mean difference in earnings manipulation, free cash flow, leverage, as well financial distress between Malaysia, Thailand and Indonesia. Study on overall data amounting 582 samples from Bursa Malaysia (Malaysia), Stock Exchange of Thailand (SET) for Thailand, and also Indonesia Stock Exchange (Indonesian: Bursa Efek Indonesia) on annual basis commencing from 2015 to 2017. The purpose of this study was whether to determine the significance of variables towards discretionary accruals (earnings manipulation) within the countries shown results from past studies can be proposed for a new regulation that focuses more towards reducing the earning manipulation within the firm, as results might be helpful for firms in the near future. Moreover, to better off identify within three countries which firrns wholly manipulates earnings more than the other. The method to be used in this study; ordinary least square, also known as OSL that further testify on descriptive statisticis as well as one-way analysis of variance (ANOVA). With the methods used, dully some areas can be minimized the sum of square error that might have in the data and portray a better result for users to understand. As the sum of squares are being minimalize, the result will have a better correlation between the countries.